2020
DOI: 10.1016/j.athoracsur.2020.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Improved Remodeling With TEVAR and Distal Bare-Metal Stent in Acute Complicated Type B Dissection

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…TEVAR can expeditiously control a rupture or cover the primary entry tear to restore true lumen flow, resulting in reduced ischemic time and improvement of outcomes over medical management alone or combined with open surgery. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Collectively, accrued data demonstrate improved outcomes with TEVAR for complicated TBAD compared with open surgery or medical therapy alone. Consequently, TEVAR has become the first-line treatment for complicated TBAD.…”
Section: Pathophysiology Of Tbadmentioning
confidence: 99%
“…TEVAR can expeditiously control a rupture or cover the primary entry tear to restore true lumen flow, resulting in reduced ischemic time and improvement of outcomes over medical management alone or combined with open surgery. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Collectively, accrued data demonstrate improved outcomes with TEVAR for complicated TBAD compared with open surgery or medical therapy alone. Consequently, TEVAR has become the first-line treatment for complicated TBAD.…”
Section: Pathophysiology Of Tbadmentioning
confidence: 99%
“…Sultan et al reported improved true lumen diameters and true lumen ratios of the abdominal aorta at the 6-month follow-up, among patients with type B aortic dissection undergoing the PETTICOAT technique compared to those undergoing TEVAR alone [ 20 ]. Similarly a recent analysis by Nienaber and colleagues of the patients from the ASSIST study found significantly more false lumen thrombosis in the abdominal aorta among patients undergoing the PETTICOAT technique compared to propensity matched patients who underwent TEVAR alone [ 17 ]. These results are similar to those found by Hashizume et al and Huang et al in their cohorts of patients [ 16 , 21 ].…”
Section: Discussionmentioning
confidence: 93%
“… 20 Conversely, others have reported that bare-metal stenting may offer positive remodeling in the distal aorta. 21 , 22 , 23 , 24 , 25 Concerns have also been raised that the PETTICOAT technique may jeopardize future adjunctive endovascular procedures because of stent strut interference. Other investigators have countered that a more expanded true lumen facilitates adjunctive procedures by virtue of the increase in workspace.…”
Section: Discussionmentioning
confidence: 99%